Jehovah's Witnesses: continuity and change - Chryssides, George D. (Ashgate new religions, 2016)
Researching Jehovah's Witnesses -- Origins -- Russell -- Rutherford -- Opposition -- Organisation -- The Bible -- Ethics and lifestyle -- Worship and rites of passage -- Prophecy -- Problems and prospects